1999
DOI: 10.1007/pl00013192
|View full text |Cite
|
Sign up to set email alerts
|

Effective Hepatic Cryoablation: Does It Enhance Tumor Dissemination?

Abstract: This experimental study was designed to investigate the risk of tumor dissemination by hepatic cryosurgery and to determine the final subzero temperature required for effective hepatic tumor cryoablation. Although cryosurgery is now one of the established modalities for the treatment of some liver tumors and has been used for two decades, controversy remains regarding the final subzero temperature needed to destroy tumor masses. One experimental report has indicated that hepatic cryosurgery may enhance tumor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…On the one hand, cryoablation of a subcutaneous tumor retards the simultaneous growth of untreated tumor on the contralateral side and induces resistance to tumor rechallenge (Neel et al, 1970;Tanaka, 1982;Sabel et al, 2005;den Brok et al, 2006). On the other hand, cryoablation of the primary tumor alone is usually, but not always (El-Shakhs et al, 1999;Joosten et al, 2001), ineffective or deleterious in controlling the growth or spread of hematogenous metastases (Javadpour et al, 1979;Yamashita et al, 1982;Wing et al, 1988;Yan et al, 2006). Our studies confirm that cryoablation of local tumor as sole therapy is unable to retard the progression of metastatic cancer.…”
Section: Antimetastatic Effect Of Tumor Cryoablation 599mentioning
confidence: 99%
“…On the one hand, cryoablation of a subcutaneous tumor retards the simultaneous growth of untreated tumor on the contralateral side and induces resistance to tumor rechallenge (Neel et al, 1970;Tanaka, 1982;Sabel et al, 2005;den Brok et al, 2006). On the other hand, cryoablation of the primary tumor alone is usually, but not always (El-Shakhs et al, 1999;Joosten et al, 2001), ineffective or deleterious in controlling the growth or spread of hematogenous metastases (Javadpour et al, 1979;Yamashita et al, 1982;Wing et al, 1988;Yan et al, 2006). Our studies confirm that cryoablation of local tumor as sole therapy is unable to retard the progression of metastatic cancer.…”
Section: Antimetastatic Effect Of Tumor Cryoablation 599mentioning
confidence: 99%
“…16,19,27 In vitro studies have identified −20°C as the minimal lethal temperature for colorectal cancer 31,32 ; −25°C for renal cancer, 29,33 pancreatic cancer, 34,35 and bladder cancer 36,37 ; and −35° for liver cancer. 24,28,38 Other studies have demonstrated that the application of a repeat or double freeze procedure can elevate the minimal lethal temperature for a given cancer type. For instance, Santucci et al 36 reported a repeat freeze can elevate the lethal temperature in bladder cancer to −20°C.…”
mentioning
confidence: 99%
“…El‐Shakhs et al . 36 also failed to demonstrate that hepatic cryotherapy enhances tumour dissemination in a rat model. The different findings might be related to the difference in their study designs.…”
Section: Discussionmentioning
confidence: 98%